An Approach to Minimising Estimated Pincushion Camera Distortions - Folorunso Olufemi Ayinde; Mohd Shahrizal Sunar; Adekiigbe Adebanjo; Obasan Olukayode (Universitas Ahmad Dahlan, 2011)
Minimizing camera distortion has been a focus of recent photorealism researches. Of the several types of camera distortions, researchers concentrated on the radial distortion being the most severe part of the total lens aberrations. Often, polynomial approximations by introducing distortion-specific parameters into the camera model have been methods of evaluating distortions. Of the two types of radial distortions, barrel, is the most discussed probably because of its dominance in cheap wide-angle lenses. In this paper, an approach to estimating and minimizing pincushion distortion by using fundamental surface area properties of the distorted image is proposed. This paper is significant as it reveals the importance of the topic and its implications on the camera. Demonstrations using four camera lenses show the robustness of this technique under different focal lengths conditions. The reliability of the approach is justified by comparing the results with the physical observations using (two tailed) t-test statistic.